2011
DOI: 10.1097/nen.0b013e3182309ab1
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Agonists Accelerate Oligodendrocyte Maturation and Influence Mitochondrial Functions and Oscillatory Ca2+Waves

Abstract: We have previously shown that natural (15-deoxy-Δ-prostaglandin J2) and synthetic (pioglitazone) agonists of peroxisome proliferator-activated receptor γ (PPAR-γ) strengthen the intrinsic cellular mechanisms protecting oligodendrocyte (OL) progenitors (OPs) from oxidative insults and promote their differentiation. Here, we demonstrate that repeated administrations of PPAR-γ agonists to OP cultures accelerate their differentiation to OLs, as indicated by increased numbers of O4- and O1-positive cells that show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…In developing OLs, mitochondria act as amplifiers of Ca 2+ movements (Haak et al, 2000) and control the Ca 2+ oscillatory events, as supported by the significant correlation between ADPinduced Ca 2+ oscillations and the presence of mitochondria (Figure 2B and C;De Nuccio et al, 2011). In PPAR-γ agonist-treated OLs, both the amplitude of cytoplasmic Ca 2+ signals and probability of occurrence of the oscillatory events are increased ( Figure 2D).…”
Section: Ppar-γ Agonist-induced Oligodendro Cyte Differentiation: Invmentioning
confidence: 72%
See 4 more Smart Citations
“…In developing OLs, mitochondria act as amplifiers of Ca 2+ movements (Haak et al, 2000) and control the Ca 2+ oscillatory events, as supported by the significant correlation between ADPinduced Ca 2+ oscillations and the presence of mitochondria (Figure 2B and C;De Nuccio et al, 2011). In PPAR-γ agonist-treated OLs, both the amplitude of cytoplasmic Ca 2+ signals and probability of occurrence of the oscillatory events are increased ( Figure 2D).…”
Section: Ppar-γ Agonist-induced Oligodendro Cyte Differentiation: Invmentioning
confidence: 72%
“…In addition, we have found that rotenone, besides slowing down OL differentiation, decreases Ca 2+ oscillations and that PPAR-γ agonists are capable of counteracting the rotenone-dependent impairment of both differentiation and Ca 2+ oscillatory activity ( Figure 3C), further supporting the need of functional mitochondria for the Ca 2+ oscillatory behaviour and the proper accomplishment of OL maturation (De Nuccio et al, 2011). Taken together, these observations suggest that the increased activity of respiratory chain promoted by PPAR-γ agonists could result in an augmented ATP production and availability for ATPdependent events ultimately linked to Ca 2+ oscillations.…”
Section: Ppar-γ Agonist-induced Oligodendro Cyte Differentiation: Invmentioning
confidence: 89%
See 3 more Smart Citations